Facework and adversarial journalism in Nigerian political interviews: Facework in journalism - David Oluwatobi Esuola; Kehinde John Okunade (Journal of Language and Pragmatics Studies, 2026)
Political interviews are sites where accountability, power, and public identity are negotiated in real time. While studies of Nigerian political discourse have focused on politicians’ rhetorical strategies, journalists’ role as active face managers has received limited attention. Based on Brown & Levinson’s Face Acts Theory (1987), this article analyses how face-threatening, face-saving, and face-repair moves appear in Rufai Oseni's political interviews on Arise TV. Through a qualitative discourse pragmatics approach on eight purposely chosen excerpts, this article demonstrates that face acts not only fulfill a politeness function but also occur within expert identity building and power negotiation. The results show that face-threatening moves in journalistic practices in the Nigerian media context appear to be socially accepted strategies of adversarial accountability. This article adds to political discourse pragmatics literature by arguing in favour of context-sensitive practices in facework, rather than relying on Cook's ideal models developed in Western contexts and adapted to other continents like Africa.